Statistical analysis study on optimization of 4-acetylpyridine thiosemicarbazone as corrrosion inhibitor - Mohamad Alwi, Muhammad Ammar; Ahmad, Mohammad Norazmi; Abdullah, Erna Normaya (2020)
4-Acetylpyridine thiosemicarbazone (4-APT) was identified to have the properties of corrosion inhibitor towards copper strips. Hence, the purpose of this research was to optimize the 4-APT by using Response Surface Methodology (RSM). The optimum result obtained of inhibition efficiency response was 89.89 %. The adsorption of 4-APT on the copper strip surface obeys the Langmuir isotherm, and the thermodynamic parameters were also determined and discussed. The potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) measurements were carried out which the results show that 4-APT is a good corrosion inhibitor, retarding both cathodic and anodic reactions in hydrochloric acid. In addition, the surface morphology of copper strip was examined with scanning electron microscopy (SEM) and the binding energy by XPS showed the protective effect of inhibited solutions. Then, the correlation between the interaction of corrosion inhibition efficiency and electronic properties of inhibitors was investigated by using density functional theory and molecular dynamic method. Theoretical results clearly showed that 4-APT exhibit good inhibition based on high energy gap and binding interaction energy.